Case Report: Surgical Reconstruction of a Massive Thoracic Wall Defect After the Resection of an Undifferentiated Radiation-Induced Sarcoma of the Breast - Rastrelli, Marco; Di Prata, Claudia; Marconato, Roberto; Del Fiore, Paolo; Granziera, Elisa; Brunello, Antonella; Vindigni, Vincenzo; Zuin, Andrea; Sbaraglia, Marta; Tropea, Saveria; Mocellin, Simone (Frontiers in Surgery, 2021)
A 54 y-old lady was referred to our institute for a massive thoracic neoplasm arising from the thoracic wall which infiltrated and dislocated the left breast. Twenty years before the patient had undergone a quadrantectomy with axillary dissection for an infiltrating ductal carcinoma of the left breast, followed by adjuvant radiotherapy and chemotherapy.A tru-cut biopsy of the mass showed a low differentiated malignant neoplasm with spindle-shaped cells . The patient underwent a total-body CT-scan which showed a 16x15x10 cm, largely necrotic mass with irregular and undefined margins with little omolateral round-shaped cervical and mesenteric lymph-nodes but no distant metastases.After a multidisciplinary discussion we proposed surgery as first therapeutic option. The planned treatment was a wide excision of the mass with the underlying ribs (II-VI) followed by reconstruction of the thoracic wall using titanium bars covered by acellular porcine dermis, latissimus dorsi flap and finally skin grafts from the thighs.